Vasiliy Davydov: The Founder of Activity Practice in Education - Gromyko Y.V (Moscow State University of Psychology and Education, 2020)
The paper analyzes the conceptual framework of the activity-based content of education that was elaborated by Vasiliy Davydov and implemented in a new design of school subjects. The article shows that, in order to promote activity practice in education, Davydov had to develop three project-oriented notions that he integrated into a single system of activity practice: 1. The notion of the structure of the thinking act - the 'cell' of any thinking processes acquired by students; 2. The notion of the concept as a system of actions (i.e. the concepts from school subjects, such as 'number', 'phoneme') that represents the main content of primary education; 3. The notion of a schoolchild's learning activity as a form of activity aimed at mastering new types of school subjects. The integration of these three notions was possible due to Davydov's metacognitive approach that allows one to analyze the concretization of the notions about the thinking act using the materials from different school subjects, in different types of activity. The paper argues that the next step in the development of activity practice in education requires the elaboration of the concept of education as a form of integration of the student's learning activity and the teacher's instructional activity.